2021
DOI: 10.1017/s1537592721000049
|View full text |Cite
|
Sign up to set email alerts
|

Who Do You Trust? The Consequences of Partisanship and Trust for Public Responsiveness to COVID-19 Orders

Abstract: Non-uniform compliance with public policy by citizens can undermine the effectiveness of government, particularly during crises. Mitigation policies intended to combat the novel coronavirus offer a real-world measure of citizen compliance, allowing us to examine the determinants of asymmetrical responsiveness. Analyzing county-level cellphone data, we leverage staggered roll-out to estimate the causal effect of stay-at-home orders on mobility using a difference-in-differences strategy. We find movement is sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 65 publications
4
56
0
1
Order By: Relevance
“…However, the impact of conspiracy theories and anti-vaccine attitudes on intention to vote for PPs in power is less accentuated when compared with the likelihood of voting for the two PPs in the opposition. In this sense, the role played by the Movimento 5 Stelle (M5S) during the vaccination campaign may have contributed to mitigate the impact of these variables on the intention to vote for PPs (Valeriani et al, 2021; see also Goldstein and Wiedemann, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of conspiracy theories and anti-vaccine attitudes on intention to vote for PPs in power is less accentuated when compared with the likelihood of voting for the two PPs in the opposition. In this sense, the role played by the Movimento 5 Stelle (M5S) during the vaccination campaign may have contributed to mitigate the impact of these variables on the intention to vote for PPs (Valeriani et al, 2021; see also Goldstein and Wiedemann, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigate the association of political attitudes and vaccine hesitancy. The partisan effect was found in studies on COVID-19 measures; many of these studies using US data found Republicans to be more vaccine-hesitant [11] , [12] , [13] . Other studies based on data in democracies found that the divide was not between the left and the right, but rather how far one was from the center, with the far-right and far-left showing more hesitancy [14] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies based on data in democracies found that the divide was not between the left and the right, but rather how far one was from the center, with the far-right and far-left showing more hesitancy [14] , [15] , [16] . A co-partisan effect has been found in which supporters follow advice from leaders of their political parties [11] . For example, a study based in Brazil found that supporters of the President strongly rejected Chinese vaccines because the President was critical of China [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Democrats, the more liberal political party in the U.S., had much greater confidence that scientists would act in the best interest of the public; while Republicans', the more conservative political party, confidence remained flat (Funk et al, 2020). Partisan opinions paralleled behavioral differences: Republicans participated in social distancing practices less than Democrats (Allcott et al, 2020;Goldstein & Wiedemann, 2021;Kushner Gadarian et al, 2020;Painter & Qiu, 2021). For example, due to the politicization of mask-wearing to prevent the spread of droplets (Thacker, 2020), the acceptability of and adherence to mask-wearing varied among the U.S. population, despite evidence that masks reduced the transmission of COVID-19 (Malecki et al, 2021).…”
Section: Introductionmentioning
confidence: 99%